Characterisation of seed marking types in chickpea (Cicer arietinum L.): Tiger stripe and other blemishes. Issue 2 (16th February 2020) - Wood, Jennifer A.; Egan, Narelle E.; Keir, Catherine F.; Miller, Julie C.; Pengilley, Georgina C.; Hobson, Kristy B.
Abstract: Desi chickpea is a significant export crop for Australia; Australia being the largest exporter globally. Visual appearance of the seed is an economically significant measure of seed quality by the Indian subcontinent, the major importer of desi chickpea worldwide. Any visual blemish on the seed is considered undesirable, regardless of the cause (biotic or otherwise). Literature on biotic causes of seed blemishes, such as ascochyta blight, are available; however, little could be found on abiotic blemishes. Abiotic seed blemishes caused by physiological plant responses are more commonly known as seed markings. Despite the presence of seed markings being confirmed by several chickpea‐producing countries during personal discussions (India, Canada), no scientific literature has been published. The aim of this study was to proactively seek out and characterise different types of seed marking patterns using a wide genetic pool of desi chickpea across a range of environments in Australia. Thirteen different seed marking patterns were identified in desi chickpea and three in kabuli chickpea, including several rare seed markings that were discovered, photographed, and described. Seed markings (blemishes thought to be caused by physiological plant stress) can be characterised as dark patterns on the testa (seed coat) that do not visually affect the underlying cotyledon. In contrast, other seed blemishes (caused by pests and disease, physical damage, or poor storage) were more likely to affect the cotyledons underlying the testa, but not always. This paper classifies and describes various types of seed markings and blemishes for future reference by the global chickpea industry.